Acute-on-chronic liver failure before liver transplantation does not impact post-transplant survival in children with biliary atresia. Issue 5 (3rd May 2023) - Banc-Husu, Anna M.; Hall, Matt; Thurm, Cary; Whitehead, Bridget A.; Godown, Justin A.; Alonso, Estella M.
Abstract : Acute-on-chronic liver failure (ACLF) occurs in children with biliary atresia (BA) awaiting liver transplantation (LT). However, data on transplant outcomes in ACLF are limited. Our aim was to characterize ACLF and determine its effect on transplant outcome and resource utilization. Using a linkage of the Scientific Registry of Transplant Recipients and Pediatric Health Information System, we identified children with BA between 3 months and 18 years at the time of listing who received a transplant from 2003 to 2018 and were hospitalized while waiting. ACLF was defined by the presence of at least 1 extra-hepatic organ failure during a pre-LT hospitalization. In all, 1044 patients (58% female, median age at listing 7.0 months IQR 5.0–14.0) were included. Thirty-four percent (351/1044) of the patients had at least 1 ACLF hospitalization. Patients with ACLF had longer waitlist times (114 [54–231] vs. 81 [35–181] days, p < 0.001), and were more likely to be listed as Status 1 (8% vs. 4%, p = 0.02). Pre-LT resource utilization was significantly higher in ACLF patients. There were no differences in mortality at 30 days (ACLF 3% vs. No ACLF 2%, p = 0.17), 90 days (ACLF 3% vs. No ACLF 2%, p = 0.24), 1 year (ACLF 3% vs. No ACLF 2%, p =0.23), 3 years (ACLF 4% vs. No ACLF 3%, p = 0.58), or 5 years (ACLF 5% vs. No ACLF 4%, p = 0.38) after LT. ACLF status was not associated with increased post-transplant mortality (adjusted HR 1.51, 95% CI 0.76–3.0, p =0.25). ACLF is an important morbidity in children with BA awaiting LT as it is associated with higher resource utilization and longer waitlist times. Further studies are needed to help understand the spectrum of ACLF and better prioritize critically ill children awaiting LT, as our study shows successful post-LT outcomes in children with BA and ACLF.